IoT‐TDMA: A performance evaluation of TDMA scheme for wireless sensor networks with Internet of Things. (17th May 2022) - Kosunalp, Selahattin; Kaya, Yunus
Abstract: This article focuses on the design and implementation of an improved version of TDMA scheme for wireless sensor networks (WSNs) exploiting the Internet of Things (IoT) phenomena. The main motivation behind this work is to create an environment for WSNs to benefit from IoT opportunities. An extensive review of the state‐of‐the‐art medium access control (MAC) approaches proposed for IoT is carried out underlying their basic principles and features. An adaptation of TDMA strategy, called IoT‐TDMA, is proposed to enhance the channel performances particularly throughput and latency. To test the performance of IoT‐TDMA practically, a low‐cost node hardware with the capability of Internet connection is essentially designed. IoT‐TDMA has been implemented on real‐world highly scalable single‐hop and multi‐hop topologies. Performance results indicate significant improvements in terms of channel throughput and end‐to‐end delay in comparison to a recently proposed efficient MAC scheme.